Privasi dalam Dunia Digital (Analisis QS. An-Nur (24): 27 Menggunakan Pendekatan Ma’na-Cum-Maghza) - Khairul Fikri; Umi Wasilatul Firdausiyah (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2021)
Abstract: Problems that still often arise in social life today are ethical issues, especially in terms of maintaining privacy, both in the real world and in the virtual world (digital). Starting to lose awareness of asking for permission and waning understanding of the boundaries of privacy has the potential to cause various problems and even criminal acts in the future. So it is important to describe how the Qoran teaches adab isti'dzan (asking permission) to take moral values ​​and practice them in life. Through the ma'na-cum-maghza approach, this paper aims to analyze QS. An-Nur (24): 27 regarding how the Qoran talks about the ethics of asking for permission and its relation to maintaining privacy. This is done in order to prove that the Qoran is still shalih li kulli zaman wa makan (relevant for every time and place) and can be used as a reference in solving contemporary problems. The results of this study indicate that the Qoran through QS. An-Nur (24): 27 not only prohibits entering the house without the permission of the owner, but it can also be understood in the current context that it contains a prohibition not to disturb other people's personal data in the digital world so thatcyber crimecan be avoided.